Teacher professionalism competency in islamic junior high school no 2 of oku timur district - Seprawanti Seprawanti; Bukman Lian; Alhadi Yan Putra (Journal of Educational and Learning Studies, 2021)
Based on the background described before, Islamic Junior High School no 2 of OKU Timur district can continue to strive for a better willingness to teach for teachers and the use of appropriate learning tools such as curriculum creation. The willingness of the teacher in the classroom is very important because after all a teacher will definitely be a foundation for students to maintain their knowledge and skills. If the teacher teaches with a heavy heart, it will certainly cause dissatisfaction which will be shown by students after experiencing the learning process. This research is a qualitative research. The researcher uses qualitative research complete the objectives of this study. The scope of this research is in Islamic Junior High School no 2 of OKU Timur district. This research uses interview techniques as one of the collecting data tools. In this case, the informants who will be interviewed are the Head of Islamic Junior High School no 2 of OKU Timur district and 4 teachers. The purpose of this research is to find out how the Competence of Teacher Professionalism in Islamic Junior High School no 2 of OKU Timur district. Based on the results of research where the ability to master scientific material, structures, concepts and mindsets that support the subject matter being taught is good, able to master the standard of proficiency and skills of core subject matter is very capable, the development of creative learning materials is still lacking, the ability to develop professionalism in a sustainable manner with taking wise action is good, the ability to use information and communication technology to communicate and develop is still lacking, the ability to understand and apply learning methods is quite capable, the ability to organize and implement learning programs is quite capable, the ability to assess student learning outcomes is very capable.